The Impact of Customer Relationship Management (CRM) on Achieving Customer Loyalty of CV. Tifa Permai Medan: Dampak Customer Relationship Management (CRM) Terhadap Tercapainya Loyalitas Pelanggan CV. Tifa Permai Medan - Benny Lim; Mega Sanjaya; Darwan Tanady; Elyzabeth Wijaya; Agus Susanto (Jurnal Kolaboratif Sains, 2024)
As the traditional economy disappeared competition increasingly appears in the new dimensions, customers become the main elements of all organizational activities. A lot of companies are not just attracting customers, but are working at building long term relationships with customers. Knowing your customers better will enable you to serve them better and keep them loyal forever. This is the main theme of Customer Relationship Management (CRM). Customer loyalty, on the other hand, is the result of an organization’s creating a benefit for customers so that they will maintain and increasingly repeat business with the organization. CV.TIFA PERMAI finds out some of their customers no more coming back to use their service or buying their product. They also find out there it’s difficult to see a reliable and holistic view of all customer interactions. From this problem caused them to lost revenue of mishandling and losing potential sales opportunities. With intense competition and the recession of sale has been difficult maintain of customer loyalty for companies nowadays. The problem identifications in the company are “How strong does customer relationship management impact on achieving the customer loyalty at CV. Tifa Permai Medan?” The writer uses the indicators of customer relationship management are information sharing, customer involvement, long-term partnership, joint problem solving, and technology based CRM by Ru-Jen, Chen, and Chiu (2010) and according to Lehman and Winer ( 2005:240) the indicators of customer loyalty are aware, repeated purchase, attracted/ happy, more order and advocates. In analyzing data, the writer used some methods such as statistics, the validity test, reliability test, normality test, correlation test, determination test, linear test, and hypothesis test. According to the result calculation data through the answers of the respondents, the writer got the result which means that customer relationship management has a strong impact on achieving the customer loyalty at CV. Tifa Permai Medan. From the calculation of determination test, the writer found out and concluded that customer relationship management has impact on achieving the customer loyalty.